Justice and reconciliation in the International Criminal Tribunal for the Former Yugoslavia - Fatić Aleksandar; Bulatović Aleksandra (Međunarodni Problemi, 2008)
By discussing the general philosophy of punishment in its contours, the authors attempt to establish conceptual connections between the philosophical roots of international criminal law for war crimes and reconciliation as an overarching goal of international criminal justice. Reconciliation is discussed in the paper both as a value and as a process and the authors strive to practically underline the issue of the capability of the International Criminal Tribunal for the Former Yugoslavia (ICTY) to actually serve the purpose of reconciliation. The authors conclude that the ITCY suffers from substantial deficiencies in its capability to effect reconciliation, not because it is politically biased, as is often remarked by analysts, but rather because of procedural and substantive legal problems encountered in its operation that shape it as less than an adequate criminal court generally speaking.